Breyten Breytenbach in een zijspiegel: Het vizier van H.C. ten Berge Transnationale laterale beweging en particuliere “hetero-images” van een literaire actor/ Breyten Breytenbach Through H.C. ten Berge’s Looking-Glass: Transnational Lateral Movement and Particular “Hetero-Images” of a Writer - T’Sjoen, Yves (Werkwinkel, 2015)
At the end of the 1960s and in the beginning of the 1970s the South African poet Breyten Breytenbach had poetry and drawings published in the leading literary magazine Raster. The editor in charge at the time, H.C. ten Berge, gave the experimental writer and socially engaged Sestiger (the literary modernizing movement in South Africa in the sixties) pride of place in the line-ups of the Dutch modernist periodical. In the seventies, Ten Berge contributed to Vingermaan (1980), a collection of poems by Dutch writers (Lucebert, Kopland, Kouwenaar, Schierbeek) in support of the anti-apartheid activist. From 1975 Breytenbach was imprisoned in South Africa for political reasons. He served seven years of a nine year sentence. At that time, in the eighties, the Netherlands organized a cultural and economical boycott against the racist regime in Pretoria. Later on, Ten Berge presented his own poems dedicated to Breytenbach in his book of poetry Nieuwe gedichten (1981) and in the collection Materia prima: Gedichten 1963-1993 (1993). Before and during the imprisonment of Breytenbach Ten Berge played an important role in the introduction of the writer in the Low Countries. From a cultural-sociological point of view Breytenbach’s presence in the Dutch language area can be described, in the terminology of Francoise Lionnet and Shu-mei Shih and later on used by Louise Viljoen, as a transnational lateral movement in his writing career. This paper deals with the cultural transmission of an important political and experimental author in the literary system of Afrikaans and English in South Africa into the Dutch system. From a bibliographical viewpoint this paper affords special attention to the publication of Breytenbach’s volume of poetry in Skryt: Om ’n sinkende skip blou te verf ([1972] 1976), Vingermaan (1980) and Nieuwe gedichten ([1981] 1987). Ten Berge played an important role in the introduction of Breytenbach to the Low Countries in the way he presented the author’s political and aesthetic ideas to a Dutch-speaking audience.